2016
DOI: 10.4274/jcrpe.3253
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone and Inhibin-A, but not Inhibin-B or Insulin-Like Peptide-3, may be Used as Surrogates in the Diagnosis of Polycystic Ovary Syndrome in Adolescents: Preliminary Results

Abstract: Objective:Polycystic ovary syndrome (PCOS) is a common endocrine problem in adolescents with an increasing prevalence of 30%. Pursuing new biomarkers with high specificity and sensitivity in the diagnosis of PCOS in adolescents is currently an active area of research. We aimed to investigate the diagnostic value of anti-Müllerian hormone (AMH), insulin-like peptide-3 (INSL3), inhibin-A (INH-A), and inhibin-B (INH-B) in adolescents with PCOS and also to determine the association, if any, between these hormones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 55 publications
1
28
0
3
Order By: Relevance
“…Reduced inhibin βA may serve as a potential diagnostic biomarker for PCOS detection. In contrast, Yetim et al reported that the dimeric inhibin A level in serum of PCOS patients was significantly higher than that in controls [28]. The reasons for the different expression of inhibin βA or dimeric inhibin A in patients with PCOS may be as follows.…”
Section: Discussionmentioning
confidence: 76%
“…Reduced inhibin βA may serve as a potential diagnostic biomarker for PCOS detection. In contrast, Yetim et al reported that the dimeric inhibin A level in serum of PCOS patients was significantly higher than that in controls [28]. The reasons for the different expression of inhibin βA or dimeric inhibin A in patients with PCOS may be as follows.…”
Section: Discussionmentioning
confidence: 76%
“…Mean, Childhood: Lee, Cui, Savas‐Erdeve, Sahin and Korkmaz . Median, Adolescence: Lee, Lashen, Anderson, Pinola, Elchuri, Cui, Hart, Hernandez and Yetim . Mean, Adolescence: Lee, Elchuri, Cui, Akin, Kim, Reinehr and Sophor…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five studies reported serum AMH levels between 10 and 18 years Only five studies reported serum inhibin levels, and only three reported AFC in adolescence . Following a transient decrease at puberty as detailed above, a broad consensus across studies show constant levels of serum AMH during adolescence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations